Autoimmune Thrombotic Thrombocytopenic Purpura: Two Rare Cases Associated with Juvenile Idiopathic Arthritis and Multiple Sclerosis - Dimopoulou, Despoina; Dimosiari, Athina; Mandala, Eudokia; Dimitroulas, Theodoros; Garyfallos, Alaxandros (Frontiers in Medicine, 2017)
Secondary thrombotic microangiopathies are associated with several underlying conditions, with most of them being resolved after the treatment of background disease. Thrombotic thrombocytopenic purpura (TTP) is a rare microangiopathy presenting with anaemia, thrombocytopenia and neurological deficits, occurring most often in various autoimmune diseases due to inhibition of ADAMTS13 by autoantibodies, as well as in pregnant women with or without an autoimmune substrate. In this article, we report two newly diagnosed TTP cases that have not been published so far. The first is a 27-year-old woman with a history of polyarticular rheumatoid factor negative juvenile idiopathic arthritis, who presented with thrombocytopenia, anaemia with schistocytes on blood smear, headache and active arthritis and was treated successfully with plasma exchange, intravenous prednisone and vincristine, while a few months after the TTP episode she was put on rituximab, resulting in remission of primary disease and no relapse of TTP. The second case refers to a 29-year-old pregnant woman coming to the ER complaining of dizziness and fatigue with microangiopathic haemolytic anaemia, low platelets count, treated with plasma exchanges, intravenous prednisolone and INN human normal immunoglobulin, resulting in full remission of the TTP episode. Six and half years later she was diagnosed with multiple sclerosis and was commenced on Interferon beta-1 alpha, with no recurrent episode of TTP. These cases broaden the spectrum of autoimmune disorders manifested or complicated clinically with TTP, an association explained from the increased disease-related propensity to form autoantibodies to ADAMTS-13. Furthermore, biological agents such as rituximab appear to be an effective treatment option for refractory cases of TTP related to systemic rheumatic disease, indicating an alternative therapeutic solution in persistent cases of this disorder.